Non‐Coding RNA Analysis Using the Rfam Database. Issue 1 (5th June 2018) - Kalvari, Ioanna; Nawrocki, Eric P.; Argasinska, Joanna; Quinones‐Olvera, Natalia; Finn, Robert D.; Bateman, Alex; Petrov, Anton I.
Abstract: Rfam is a database of non‐coding RNA families in which each family is represented by a multiple sequence alignment, a consensus secondary structure, and a covariance model. Using a combination of manual and literature‐based curation and a custom software pipeline, Rfam converts descriptions of RNA families found in the scientific literature into computational models that can be used to annotate RNAs belonging to those families in any DNA or RNA sequence. Valuable research outputs that are often locked up in figures and supplementary information files are encapsulated in Rfam entries and made accessible through the Rfam Web site. The data produced by Rfam have a broad application, from genome annotation to providing training sets for algorithm development. This article gives an overview of how to search and navigate the Rfam Web site, and how to annotate sequences with RNA families. The Rfam database is freely available at http://rfam.org . © 2018 by John Wiley & Sons, Inc.